New Optical Designs for Large Parabolic Troughs - Canavarro, Diogo (2022)
The potential for cost reduction in parabolic troughs (PT) large collector fields is real and will be achieved in a variety of different ways. One problem certainly contributing to the costs of Solar Thermal Electricity (STE) PT fields is certainly the fact that large fields have a significant quantity of receiver lines and pipes bringing the heat transfer fluid to and off from them. The very large pipe length in large collector fields (for instance the 50MW fields in Spain) is a source of heat losses and parasitic losses due to significant pumping power, but also a source of other costs related to the number of pumps, to the amount of (costly) circulating fluid etc. In any given large field, receiver length and pipe length are determined by the aperture size of the PTs and one way to reduce these impacts on cost would be to increase aperture size. This has been the idea behind developments like the Ultimate Trough. In this paper new optical solutions are presented to obtain much larger troughs, using the same “standard” evacuated 70 mm inner radius tube, which in fact amounts to a substantial increase of concentration, but without sacrificing the acceptance angle of the optic. The Simultaneous Multiple Surface (SMS) method is used and practical solutions are obtained for apertures nearly close to twice the present standard of ≈ 6m width. The case of troughs for fixed receiver tubes is also discussed in this context. The solutions developed minimize transmission losses due to the glass cover and in that sense are an improvement on previous work. They also achieve a higher optical performance than other second stage solutions, because they are designed to eliminate optical losses through large gaps, something that is associated with the fact that the outer glass envelope has a much larger diameter than the inner receiver tube. The paper presents new examples of larger troughs with second stage concentrators, characterizing and comparing them with a “conventional” PT. The comparison is done for optical properties and for the energy collected on a sunny location (Faro, Portugal). The paper ends with a similar exercise done for fixed receiver troughs, an exercise that also leads to larger troughs (since it is done for the same 70 mm inner (evacuated) receiver tube) and concentration is increased. Again optical properties and energy performance are presented and compared with the conventional PT. The new solutions represent a potential reduction in field costs or even in O&M, as suggested, and this exercise will enable manufacturers the pondering of the manufacture of larger troughs (perhaps cheaper on a sqm basis) but with the extra cost of a secondary concentrator, knowing how much energy to expect from the adoption of solutions that benefit non-imaging optics design methods.